Gender difference in the chinese middle-aged and elderly of pocket park use: A case study of zongbei park - Li, Yaru; Niu, Shaofei; Mou, Yanchuan (Frontiers in Environmental Science, 2022)
Public parks are critical resources for physical activity (PA). Pocket parks within neighborhoods play an essential role in the elder' daily life. A deep understanding of pocket park use and park-based PA for older adults supports the better design of outdoor spaces. Gender differences have been confirmed in previous studies. Indeed, it was observed that more males visit parks than females, and males are likely to be vigorously active. However, almost all the studies were conducted in western countries, and none has yet focused on the Chinese elderly. The main objective of this study is to investigate gender differences in park-based PA in the Chinese middle-aged and elderly population. In Zongbei Park (Chengdu, China), video recording is used from 07:00 am to 07:00 pm to document numbers, gender, age group, and type of activity. Demographic variations of park use patterns and energy expenditure are analyzed. The study findings indicated that most users (92.05%) were middle-aged and elderly. Significant gender variations were found in the number of total and five types of activities (p < 0.01), respectively. Although more old males than females were observed in Zongbei Park, the total METs and mean METs per male were lower than females. A majority (65.66%) of the older adults were seen playing cards/mahjong. It will lead to a significant number of sedentary older adults. As China faces severe healthcare challenges due to the problem of aging, it becomes essential to construct age-friendly design pocket parks. More attention should be paid to address the park-based PA gender gap.